Design of a Hybrid Refractive/Diffractive Lens System for Broadband UV - Yuan Hu; Jiaqi Huo; Binpeng Cheng (Sensors, 2022)
Traditional broadband UV optical designs often have complex structural problems and cannot meet the current requirements of light and miniaturization. In this study, we first design the substrate material of double-layer diffractive optical elements (DOEs) in the 0.23–0.8 μm band, optimize the diffraction efficiency and analyze the effect of the angle of incidence on the diffraction efficiency of double-layer DOEs. Second, we design a refractive lens system and a refractive/diffractive hybrid lens system with double-layer DOEs designed for a wide UV wavelength range of 0.23–0.8 μm, a half field of view of 15 mm, an objective aperture of 0.1 and a magnification of 1. The refractive/diffractive hybrid lens system designed with seven lenses produces a higher image quality than the refractive lens system. The novel design is an effective solution to the problem of the low transmission rate of traditional UV refractive lens systems.